2020
DOI: 10.1093/mnras/staa022
|View full text |Cite
|
Sign up to set email alerts
|

Cosmic rays escaping from Galactic starburst-driven superbubbles

Abstract: We calculate spectra of escaping cosmic rays (CRs) accelerated at shocks produced by expanding Galactic superbubbles powered by multiple supernovae producing a continuous energy outflow in star-forming galaxies. We solve the generalized Kompaneets equations adapted to expansion in various external density profiles, including exponential and power-law shapes, and take into account that escaping CRs are dominated by those around their maximum energies. We find that the escaping CR spectrum largely depends on the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 60 publications
(80 reference statements)
1
6
0
Order By: Relevance
“…5 and it is compared with observations by Fermi-LAT 29 , IceCube 30 , IceTop 34 , Tunka 31,32 and Kascade-Grande 33 . While the total gamma-ray flux from SB-driven wind bubbles contributes approximately to ∼ 5 − 10% of the Fermi-LAT data, leaving enough room for SBNi 35,36,37,38 and AGNi 16,39 , the total neutrino flux and the associated CR flux could provide a sizeable contribution and possibly saturate part of the observed spectra 14,40 .…”
Section: Discussionmentioning
confidence: 99%
“…5 and it is compared with observations by Fermi-LAT 29 , IceCube 30 , IceTop 34 , Tunka 31,32 and Kascade-Grande 33 . While the total gamma-ray flux from SB-driven wind bubbles contributes approximately to ∼ 5 − 10% of the Fermi-LAT data, leaving enough room for SBNi 35,36,37,38 and AGNi 16,39 , the total neutrino flux and the associated CR flux could provide a sizeable contribution and possibly saturate part of the observed spectra 14,40 .…”
Section: Discussionmentioning
confidence: 99%
“…A new solution for the 1D diffusion equation with losses proportional to the concentration was derived, see Equations ( 13) and (14).…”
Section: Conclusion Diffusion With Stationary Statementioning
confidence: 99%
“…analysis of the generalized Kompaneets' equations adapted to expansion in various external density profiles and coupled with escaping CRs [14], production of γ-ray radiation in the interactions between cosmic rays and interstellar gas in the Orion-Eridanus SB [15] and acceleration of particles and non-linear feedback [16]. Another point for research is the excess in γ-rays observed by the Fermi Large Area Telescope at the centre of the Galaxy, which can be explained by annihilating dark matter, [17].…”
Section: Introductionmentioning
confidence: 99%
“…Superbubbles may accelerate cosmic rays up to PeV energies or beyond via multiple shocks and turbulence (Bykov & Fleishman 1992;Klepach et al 2000). It has been shown that cosmic rays escaping from star clusters or superbubbles may explain cosmic rays above the knee energy (Murase & Fukugita 2019;Zhang et al 2020). The Cygnus region has also been of much interest as the promising source of high-energy neutrinos (e.g., Anchordoqui et al 2007;Beacom & Kistler 2007;Halzen & O Murchadha 2007;Halzen et al 2017).…”
Section: Contribution Of Discrete Sources To Sub-pev Gamma Rays and N...mentioning
confidence: 99%